2022
DOI: 10.2196/33656
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Self-reports and Photos to Assess e-Cigarette Device and Liquid Characteristics in Wave 1 of the Vaping and Patterns of e-Cigarette Use Research Study: Web-Based Longitudinal Cohort Study

Abstract: Background e-Cigarette device and liquid characteristics are highly customizable; these characteristics impact nicotine delivery and exposure to toxic constituents. It is critical to understand optimal methods for measuring these characteristics to accurately assess their impacts on user behavior and health. Objective To inform future survey development, we assessed the agreement between responses from survey participants (self-reports) and photos uploa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Nicotine concentration, on the other hand, presents additional measurement challenges; however, the strategy utilized in this paper in which photo and self-report data are used in tandem may optimize data quality. ( Crespi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine concentration, on the other hand, presents additional measurement challenges; however, the strategy utilized in this paper in which photo and self-report data are used in tandem may optimize data quality. ( Crespi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, post-stratification weights ranging from 0.64 to 1.56 were applied to improve representativeness. The data quality and quantity is optimized by employing a range of data integrity procedures and by using photo data of devices and liquids 13,29 . We examined the transition of ENDS device/liquid grouping rather than device type alone, which allows exploring key variability influencing nicotine delivery 14,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The data reported here were captured directly from participant photos of their devices and liquids and from manufacturer, academic, retail, and review sites; therefore, these data are only as accurate as the photos and sites utilized for coding. However, previous research has suggested that self-reported and photo-coded device type and flavor have a high agreement, suggesting a fair level of accuracy with these data 36 . As mentioned in the results, the increased identification of products across waves may account for some of the increase in liquid products across waves; however, the increase in the proportion of liquids identified is more likely driven by the decreasing prevalence of disposable pod devices, for which photos often do not include the flavor or nicotine concentration of the product because this information is often not included on the pod itself.…”
Section: Discussionmentioning
confidence: 73%